The Effect of Lime Chitosan Concentration And Storage time on the Quality of Fresh Tofu - Brananda Hasiholan Perangin-angin; Terip Karo-Karo; Herla Rusmarilin (Universitas Sumatera Utara, 2013)
The research was conducted to determine the effect of lime chitosan concentration and storage time on the quality of fresh tofu. This study used a completely randomized design with two factors is: lime Chitosan concentration (K) : 0.25%, 0.5%, 0.75%, 1% and 1.25% and storage time (P) : 5, 10, and 15 days. The parameters analyzed were moisture content, ash content, total microbes, pH, protein content, and sensory characteristics (color, flavor and aroma, and texture). The results showed that the lime chitosan concentration had highly significant effect on all parameters and sensory characteristics. Storage time had highly significant effect on all parameters and sensory characteristics. Interaction of both factors had highly significant effect on total microbial, pH, protein content, and color, flavor and aroma. Lime chitosan concentration of 0.5% was the best treatment for the fresh tofu.